EMPLOYMENT ABSORPTIVE CAPACITY OF SMALLHOLDER COFFEE PLANTATIONS AND SUSTAINABLE COFFEE DEVELOPMENT IN JEMBER DISTRICT - Ebban Bagus Kuntadi; Joni Murti Mulyo Aji; Dewi Churva H. Sholihah (UPT Penerbitan Universitas Jember, 2017)
Jember District is the second largest of coffee producing area in East Java (after Malang) with coffeeplanted area around 5,608 hectares. Based on the data in 2012, 27 of 31 sub districts in Jember arecoffee producers which means only 4 sub-districts in this region do not produce coffee. Each area,however, has a different potency on coffee production. To understand the role of coffee in the regionaldevelopment, an area mapping on distribution of smallholder coffee plantation is therefore needed asit related to labor employment in plantation sector, particularly as most of those run by smallholdersas well as the change of economic structure in Jember District. The importance of smallholder coffeeplantation’s role on labor absorption and economic growth on Jember will eventually determine thefurther policy on the development of smallholder coffee plantation as an important subsector inJember. This research aimed to: (1) describe the characteristic of distribution coffee plantation area bysmallholders in Jember District, (2) know the shift of GDP value from smallholder coffee in Jember,and (3) know the employment absorptive capacity on smallholder coffee plantation in Jember District.Both descriptive and analytic methods were used in this research. Methods of analysis used in thisresearch include location quotient (LQ), locality coefficient and specialization coefficient, shift-shareanalysis, demo-metric model, and contribution. The result of this study showed that (1) thecharacteristics of distribution smallholder coffee area in Jember Regency were not concentrated, (2)the shift share and position of GDP value from smallholder coffee were positive, and (3) smallholdercoffee plantation ability on producing the economic outputs and its contribution to the regioneconomic growth is followed by increasing labor absorption and have positive impacts on the districtregional development.